Evaluation of defect formation in chalcopyrite compounds under Cu-poor conditions by advanced structural and vibrational analyses. (15th January 2022) - Guc, Maxim; Bailo, Eduard; Fonoll-Rubio, Robert; Atlan, Fabien; Placidi, Marcel; Jackson, Philip; Hariskos, Dimitrios; Alcobe, Xavier; Pistor, Paul; Becerril-Romero, Ignacio; Perez-Rodriguez, Alejandro; Ramos, Francisco; et al.
Abstract: Cu-poor compositions are key for obtaining high efficiency Cu(In, Ga)Se2 (CIGSe) devices. These conditions lead to Cu deficit accommodation mechanisms like the formation of Cu-related defects in the CIGSe crystal structure or of ordered vacancy compound. However, the origin of the benefits of Cu-poor compositions is still under discussion since these mechanisms are difficult to detect and characterize. In this work, a high precision Raman spectroscopy and X-ray diffraction analysis on a compositionally-graded CISe sample ([C u ]/[In] ratios from 0.48 to 1.03) allows us to shed light on this topic by reporting the detection of a "defective chalcopyrite phase" in the slightly Cu-poor compositional regime that may play a critical role, rather than other previously discussed mechanisms, on device performance. This phase is mainly characterized by the formation of a specific defect in the CISe structure which also contributes to appearance of a Raman peak at 230 cm −1 . Finally, the analysis of high efficiency (> 18%) CIGSe solar cells and the extrapolation of the results on defect formation obtained for CISe, suggest a possible impact of the defective chalcopyrite phase on the open circuit voltage of the devices, and opens a possible way to further investigate and develop the chalcopyrite based technologies. Graphical abstract: Image, graphical abstract